High-acid-resistance ceramic glaze material and preparation method thereof

By constructing a lotus-leaf-like microconvex structure on the surface of the ceramic glaze material and introducing fluorine-doped titanium oxide and boron nitride nanosheets, the shortcomings of ceramic glaze materials in high acid resistance and self-cleaning performance are solved, and high acid resistance and long-term self-cleaning effects are achieved in a strong acid environment.

CN119874193APending Publication Date: 2025-04-25LOUDI XIANGXIN IND & TRADE CO LTD

Patent Information

Application Number
CN202510338526.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing ceramic glaze materials have shortcomings in high acid resistance and self-cleaning properties, and it is difficult to maintain stability and self-cleaning effects in strong acid or alkaline environments.

Method used

The micro-convex design is designed with a lotus leaf-like structure, combined with fluorine-doped titanium oxide and boron nitride nanosheets, forming a surface structure with micro-nano-level double roughness, enhancing the acid resistance and self-cleaning performance of the glaze layer.

Benefits of technology

It realizes the high acid resistance and long-term self-cleaning effect of ceramic glaze materials in strong acid environments, and improves the service life and environmental adaptability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874193A_ABST
    Figure CN119874193A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic glaze materials, and provides a high-acid-resistance ceramic glaze material and a preparation method thereof.The glaze is composed of boron nitride nanosheets, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, aluminum oxide, zirconium oxide, silicon carbide, sodium fluosilicate, borax, kaolin, calcium phosphate, polymethyl methacrylate balls, ammonium polyacrylate and deionized water. A lotus-leaf-like micro-convex structure is formed on the surface of the glaze layer, the convex gap is 2.5-5.0 microns, the height is 0.8-1.2 microns, and the diameter is 1.1-2.5 microns, so that the acid resistance and the super-hydrophobic property are improved. The preparation method comprises the following steps: step-by-step ball milling of a hard phase and a soft phase, high-energy ball milling assisted stripping of boron nitride, ultrasonic dispersion, template introduction, freeze drying, gradient pyrolysis under nitrogen protection, sintering at 1150-1200 DEG C, sodium fluosilicate surface fluorination treatment and the like. The stability of TiO2 is optimized through fluorine doping, the acid resistance and crack resistance are enhanced through boron nitride, and the self-cleaning property is improved through a nano structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic glaze materials, and in particular to a highly acid-resistant ceramic glaze material and a preparation method thereof. Background Art

[0002] Highly acid-resistant ceramic glaze materials have a wide range of application value in many industrial and civil fields, especially in scenes such as chemical equipment, building exterior walls, tableware, and medical devices that need to be exposed to acidic or corrosive environments for a long time. Storage tanks, pipelines, and reactors in the chemical industry are often exposed to strong acids or corrosive media, requiring the glaze layer to have excellent acid and alkali resistance to ensure the long-term stable operation of the equipment and reduce maintenance costs. In the construction field, exterior wall tiles and decorative ceramics are exposed to acid rain, pollutants, and harsh climatic conditions for a long time. If the glaze layer is not resistant to chemical corrosion, it is easy to cause surface erosion, fading, and even structural deterioration, affecting the aesthetics and service life of the building. In addition, the ceramic coatings of tableware and medical devices need to have both acid and alkali resistance and self-cleaning functions to resist chemical corrosion caused by food residues, bacterial attachment, and repeated cleaning, and improve hygiene and safety. To meet these application requirements, ceramic glaze materials need to have excellent acid and alkali resistance, be able to resist long-term erosion by strong acids (such as hydrochloric acid and sulfuric acid) and alkaline media (such as NaOH), while maintaining high mechanical strength and stability. In addition, the surface of the glaze layer must have self-cleaning properties, that is, it must exhibit super-hydrophobic properties, making it difficult for water droplets and pollutants to adhere, thereby reducing dirt accumulation, improving service life and ease of maintenance. The combination of high acid resistance and self-cleaning properties can not only increase the service life of the material and reduce maintenance costs, but also broaden its application range in extreme environments and promote the widespread application of ceramic materials in high-end industrial and civilian fields. Therefore, the development of ceramic glaze materials with both high acid resistance and self-cleaning functions is of great significance for improving product performance, reducing maintenance costs, and enhancing the market competitiveness of materials.

[0003] At present, the research on acid-alkali resistant ceramic glaze materials has made certain progress, but there are still many shortcomings, mainly reflected in the optimization of acid-alkali resistance and self-cleaning performance. For example, the Chinese patent with publication number CN107804973A discloses a ceramic glaze, which improves certain acid resistance but does not have self-cleaning performance. In addition, traditional ceramic glaze mainly relies on densification sintering process to improve corrosion resistance, but this often leads to high surface energy of glaze layer, making it difficult to form super-hydrophobic structure, thus unable to achieve self-cleaning function. Although some existing super-hydrophobic ceramic glazes based on nanoparticle modification (such as modified with silicon dioxide or titanium dioxide) have improved in hydrophobicity, nanoparticles are easily agglomerated during high-temperature sintering, resulting in reduced stability of hydrophobic layer, limited service life, and easy to be mechanically worn or chemically eroded during long-term use, so that the self-cleaning effect is attenuated. In addition, some studies have attempted to introduce fluoride into the glaze layer to enhance acid resistance and hydrophobicity, but the uniform distribution and long-term stability of fluoride are still technical difficulties. In summary, the stability of existing acid- and alkali-resistant ceramic glaze materials in strong acid and alkali environments, the durability of self-cleaning performance, and the optimization of processing technology still face challenges. Therefore, it is urgent to develop a new type of ceramic glaze material with both high acid resistance and super-hydrophobic self-cleaning functions to overcome the limitations of existing technologies and meet the needs of high-end industrial and civilian fields. Summary of the invention

[0004] The purpose of the present invention is to provide a highly acid-resistant ceramic glaze material and a preparation method thereof, so as to solve the problem that the current ceramic glaze materials are insufficient in terms of high acid resistance and self-cleaning performance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: A highly acid-resistant ceramic glaze material comprises the following raw materials in parts by weight: 1.0-2.5 parts of boron nitride nanosheets, 10-20 parts of fluorine-doped titanium oxide, 1.0-2.5 parts of calcium fluoride, 15.0-30.0 parts of kaolinite, 20.0-40.0 parts of feldspar, 40-60 parts of aluminum oxide, 15-25 parts of zirconium oxide, 5-15 parts of silicon carbide, 2.0-6.0 parts of sodium fluorosilicate, 5-10 parts of borax, 20-30 parts of kaolin, 2.0-10.0 parts of calcium phosphate, 5.0-10.0 parts of polymethyl methacrylate balls, 2-5 parts of ammonium polyacrylate, and 30-50 parts of deionized water; The average diameter of the polymethyl methacrylate spheres is 3.0-6.0 μm; The surface of the ceramic glaze material has micro-convex bodies imitating a lotus leaf structure; The micro-convex bodies have an average gap of 2.5-5.0 μm, an average height of 0.8-1.2 μm, and an average diameter of 1.1-2.5 μm.

[0006] The doping amount of fluorine in the fluorine-doped titanium oxide is 0.5-3 wt%.

[0007] The present invention adopts a design imitating a lotus leaf-like structure, which is mainly used to enhance the acid resistance and self-cleaning performance of ceramic glaze materials. By constructing a micro-convex structure with a specific size on the surface of the glaze layer, a micro-nanoscale double roughness is formed on the surface of the material, thereby reducing the surface energy, improving the hydrophobicity, and reducing the infiltration and erosion of the glaze layer by the acidic medium. In addition, the introduction of fluorine-doped titanium oxide further improves the chemical stability of the glaze layer. The presence of fluorine element changes the surface properties of titanium oxide, so that it exhibits more excellent corrosion resistance in an acidic environment, and at the same time enhances the hydrophobicity of the material, thereby synergizing the micro-convex structure to achieve an excellent self-cleaning effect. In the material system, aluminum oxide and zirconium oxide are the main skeleton components, which improve the mechanical strength and wear resistance of the glaze layer, and the addition of silicon carbide further enhances the impact resistance and high temperature resistance of the material. The reasonable ratio of feldspar, kaolinite and kaolin optimizes the sintering behavior of the glaze layer, so that the components can be evenly distributed, avoid phase separation, and ensure the structural stability of the glaze layer. The surface fluorination treatment of sodium fluorosilicate further reduces the surface energy of the material, allowing water droplets to form a spherical structure with a larger contact angle on the surface of the glaze layer, thereby further improving the hydrophobicity, reducing the attachment of pollutants, and improving the self-cleaning ability. In addition, the template effect of the polymethyl methacrylate ball forms a uniform microporous structure during the sintering process, which helps to further optimize the surface roughness, and cooperates with the micro-convex structure and fluorine-doped titanium oxide to achieve high acid resistance and excellent superhydrophobic properties. Through the synergistic effect of each component of the entire material system, the ceramic glaze layer not only has excellent acid and alkali resistance, but also can maintain a stable self-cleaning effect during long-term use, effectively improving the application life and environmental adaptability.

[0008] Furthermore, the preparation method of the boron nitride nanosheets is as follows: by weight, 2.5 to 5.5 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 180 to 220 parts of deionized water are added, and the interlayer exfoliation is achieved at an ultrasonic frequency of 38 to 42 kHz for 110 to 130 minutes, followed by centrifugation at 3000 to 5000 rpm for 8 to 12 minutes to remove the unexfoliated layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, and ethanol and deionized water are used to wash alternately 3 to 5 times in a volume ratio of 1:3, and the amount of solvent used for each washing is 40 to 60 mL / g of nanosheets, and the boron nitride nanosheets are dried in a vacuum drying oven at 55 to 65°C and -0.08 to -0.10 MPa for 4.0 to 6.0 hours to obtain boron nitride nanosheets.

[0009] Furthermore, the preparation method of the intercalated boron nitride is as follows: by weight, 1.0-2.0 parts of hexagonal boron nitride powder and 18.0-22.0 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 780-820°C at a rate of 8-12°C / min under nitrogen atmosphere protection and kept warm for 3.5-4.5h to complete the intercalation reaction, and cooled to room temperature to obtain intercalated boron nitride.

[0010] Furthermore, the boron nitride nanosheet has a thickness of 0.6-1.2 nm and a lateral size of 0.8-5.5 μm.

[0011] The present invention adopts the design of boron nitride nanosheets mainly for enhancing the acid resistance and self-cleaning performance of ceramic glaze materials. Boron nitride nanosheets are prepared by ultrasonic stripping technology to reduce the interlayer bonding force, thereby forming a two-dimensional nanosheet structure with high stability and high dispersibility. In the material system, the introduction of boron nitride nanosheets effectively improves the acid resistance of the glaze layer, and its chemical inertness and structural stability enable it to maintain integrity in a strong acid environment and avoid the erosion of the material by acidic media. At the same time, the layered structure of the boron nitride nanosheets is evenly distributed in the glaze layer, which can optimize the overall density and reduce the possibility of acidic medium penetration, thereby improving the durability of the glaze layer. In addition, the ultra-thin sheet structure of the boron nitride nanosheet can promote the uniform distribution between particles during the sintering process, improve the mechanical strength of the material, and maintain excellent crack resistance under high temperature environment. In the preparation process of intercalated boron nitride, the interlayer force is effectively reduced by the intercalation effect of potassium hydroxide, making the subsequent stripping process more efficient, ensuring the uniform dispersibility of the obtained boron nitride nanosheets in the ceramic glaze layer. Its nanometer-scale thickness and large lateral size enable it to form a stable microscopic barrier in the glaze layer, further enhancing the material's resistance to chemical erosion. In addition, the surface properties of boron nitride nanosheets enable it to reduce the surface energy of the material, synergize with other components in the ceramic glaze layer, improve the overall superhydrophobic properties, and make water droplets form a spherical structure with a high contact angle on the surface of the glaze layer, thereby effectively reducing the adhesion of pollutants and achieving an excellent self-cleaning effect. In the entire system, boron nitride nanosheets not only improve the acid resistance of ceramic glazes through their chemical stability, but also optimize the density and mechanical strength of the glaze layer at the microstructural level, and enhance the self-cleaning function by reducing the surface energy. The synergistic effect of various components enables the ceramic glaze material to operate stably for a long time in complex environments, meeting the requirements of high acid resistance and self-cleaning performance.

[0012] Furthermore, the preparation method of the fluorine-doped titanium oxide is as follows: 4.5 to 8.5 parts by weight of a fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 400 to 600 °C at 3 to 8 °C / min under a nitrogen atmosphere, kept warm for 2 to 6 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5 μm.

[0013] Furthermore, the preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 1.0-5.0 parts of titanium tetrachloride are mixed with 50-150 parts of deionized water, and stirred at 300-500 rpm for 10-30 min under a magnetic stirrer to form a transparent solution; 0.5-3.0 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 0.1 to 1.0 mol / L, the dropwise addition speed is controlled to be 0.1-0.5 mL / min, and the pH of the system is simultaneously adjusted to 2.0-4.0; the mixed solution is transferred to a high-pressure reactor, the temperature is increased to 120-180 °C at 2-5 °C / min, and the temperature is maintained for 12-36 h for hydrothermal reaction; after cooling to 25-35 °C, the precipitate is separated by a centrifuge at 8000-12000 rpm for 5-15 min. min, discard the supernatant; wash the precipitate 3 to 5 times alternately with deionized water and ethanol in a 1:1 volume ratio, and the amount of solvent used for each washing is 30 to 50 mL / g of precipitate; place the washed product in a vacuum drying oven, and dry it at 60 to 80 °C and -0.05 to -0.10 MPa for 6 to 12 h to obtain a fluorine-doped titanium oxide precursor.

[0014] The present invention adopts the design of fluorine-doped titanium oxide mainly to enhance the acid resistance and self-cleaning performance of ceramic glaze materials. The chemical structure of titanium oxide is regulated by fluorine doping, so that it exhibits more excellent stability in an acidic environment, avoiding the problem that traditional titanium oxide is prone to dissolution or structural changes in an acidic medium, thereby improving the acid resistance of the glaze layer. In the preparation process, titanium tetrachloride and deionized water form a uniform solution, and ammonium fluoride solution is added dropwise under controlled pH conditions to ensure that the fluorine element can be uniformly doped into the lattice structure of titanium oxide. Subsequently, a hydrothermal reaction is used to promote the formation of a fluorine-doped titanium oxide precursor, and a fluorine-doped titanium oxide precursor with high purity and good dispersibility is obtained through steps such as centrifugal separation, alternating washing and vacuum drying. In the subsequent tubular furnace heat treatment process, the fluorine-doped titanium oxide precursor is further crystallized and stabilized in a nitrogen atmosphere, and its particle size is optimized by controlling the temperature and insulation time, thereby ensuring its uniform distribution in the ceramic glaze layer. The introduction of fluorine doping not only improves the chemical stability of titanium oxide, but also effectively reduces its surface energy, allowing it to synergize with the microstructure in the glaze layer to enhance the overall hydrophobicity, thereby improving the self-cleaning performance. In addition, the uniform distribution of fluorine-doped titanium oxide in the glaze layer can enhance the material's corrosion resistance, and work together with other components to improve the density of the glaze layer, reduce the penetration of acidic media, and enable the ceramic glaze material to maintain stable chemical properties in a strong acid environment. Overall, fluorine-doped titanium oxide, through its unique chemical stability and surface regulation, forms a synergistic effect with other components of the ceramic glaze layer, achieving an organic combination of high acid resistance and self-cleaning performance, allowing the material to have a longer service life and better protection in complex environments.

[0015] The present invention also discloses a method for preparing a highly acid-resistant ceramic glaze material, comprising the following steps: S1. Alumina, zirconium oxide and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added to control the ball-to-material ratio to 3:1, and the mixture is milled at a ball milling rate of 400-500 rpm for 2-4 h. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate and borax are added, the ball milling rate is reduced to 200-250 rpm, and the mixture is mixed for 2-3 h. After the ball milling is completed, the obtained suspension is filtered through a 200-400 mesh sieve to remove large particle impurities and set aside. S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 300-400 rpm for 2-4 h using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing 40-60 kHz ultrasonic treatment for 30-45 min to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 300-600 rpm for 1-3 h to uniformly distribute them in the slurry. After stirring, let it stand for 30-60 min to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is uniformly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 80-120 μm. After coating, the sample is placed in a -50--40 °C environment for pre-freezing, and sublimation drying is performed at 0.1 Pa for 12-24 h; S5. Place the freeze-dried sample in a tube furnace and perform step-by-step pyrolysis under a nitrogen atmosphere. First, heat the sample to 300-320°C at a heating rate of 1-2°C / min and keep it at that temperature for 2-3 h to decompose part of the organic template. Then, heat the sample to 500-550°C at the same heating rate and keep it at that temperature for another 2-3 h to ensure that the polymethyl methacrylate balls are completely decomposed. Then, reduce the heating rate to 3-5°C / min, continue to heat the sample to 1150-1200°C and keep it at that temperature for 2-4 h to achieve the densification of the glaze layer. S6. Slowly cool the sintered sample to 600~800 ℃, and continue to cool to room temperature at a cooling rate of 2~5 ℃ / min. Subsequently, place the obtained ceramic glaze layer sample in a 0.5~2.0 mol / L sodium fluorosilicate solution and soak for 30~60 minutes. After the treatment is completed, take out the sample, bake it in an environment of 150~200 ℃ for 1~3 hours, and cool it to room temperature.

[0016] The present invention also discloses a method for preparing a highly acid-resistant ceramic glaze material, which achieves high acid resistance and self-cleaning performance of the glaze layer by precisely controlling the component ratio and multi-step optimization process. In the S1 stage, the preliminary ball milling of alumina, zirconium oxide and silicon carbide provides excellent mechanical strength and thermal shock resistance, while the synergistic effect of fluorine-doped titanium oxide and calcium fluoride significantly improves the acid and alkali resistance of the glaze layer. At the same time, kaolinite, feldspar, kaolin, calcium phosphate and borax optimize the sintering characteristics and chemical stability. In the S2 stage, high-energy ball milling and ultrasonic dispersion technology are used to uniformly introduce boron nitride nanosheets, whose layered barrier structure effectively prevents the penetration of acidic media and cooperates with ammonium polyacrylate to improve dispersion stability. In the S3 stage, polymethyl methacrylate balls are added to form a micro-nano pore structure, which together with boron nitride nanosheets enhances acid resistance and self-cleaning performance. In the S4 stage, the uniformity of the glaze layer is improved by low-temperature freezing and sublimation drying technology to prevent shrinkage and cracking. In the S5 stage, multi-step pyrolysis is used to ensure the densification of the glaze layer, while optimizing the uniform distribution of fluorine-doped titanium oxide to further improve acid resistance. In the S6 stage, sodium fluorosilicate treatment reduces surface energy, strengthens self-cleaning effect and enhances long-term acid resistance. The synergistic effect of each component, through fine structure regulation and optimized process, enables the ceramic glaze material to have excellent corrosion resistance and self-cleaning performance in extreme acidic environments, meeting the application needs of high-end industrial and civil fields.

[0017] 1. The present invention achieves high acid resistance and self-cleaning performance of ceramic glaze materials through the synergistic effect of boron nitride nanosheets and fluorine-doped titanium oxide. Boron nitride nanosheets construct an anti-penetration barrier, optimize the density of the glaze layer, and improve mechanical strength. Fluorine-doped titanium oxide enhances chemical stability, reduces surface energy, and improves hydrophobicity. Each component synergistically optimizes the microstructure, so that the glaze layer remains stable in a strong acid environment, reduces corrosion, and increases service life. It is widely used in chemical equipment, anti-corrosion building materials and high-end ceramics.

[0018] 2. The present invention optimizes the acid resistance and self-cleaning performance of ceramic glaze materials by synergistically optimizing the lotus leaf-like micro-convex structure and fluorine-doped titanium oxide, significantly reducing surface energy, and improving corrosion resistance and hydrophobicity. Alumina and zirconium oxide enhance mechanical strength, silicon carbide improves impact resistance, feldspar, kaolinite, and kaolin optimize sintering uniformity, sodium fluorosilicate surface fluorination further enhances super-hydrophobicity, and polymethyl methacrylate balls construct a microporous structure. The synergistic effect of each component improves the stability of the glaze layer, and it is widely used in the fields of anti-corrosion building materials, chemical equipment, and high-end ceramics.

[0019] 3. The present invention achieves high acid resistance and self-cleaning performance of ceramic glaze materials by precisely controlling the component ratio and optimizing the process, which is significantly better than the existing technology. Alumina, zirconium oxide and silicon carbide enhance mechanical strength, fluorine-doped titanium oxide and calcium fluoride synergistically optimize acid resistance, boron nitride nanosheets construct an anti-penetration barrier, polymethyl methacrylate balls form micro-nano pores to enhance the self-cleaning effect, and sodium fluorosilicate treatment reduces surface energy. The synergistic effect of various components enables the material to have a longer life, lower maintenance cost and better environmental adaptability in the fields of chemical industry, anti-corrosion and construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The surface of the highly acid-resistant ceramic glaze material prepared in Example 1 of the present invention has a lotus leaf-like micro-convex structure.

[0021] Figure 2 This is the water drop morphology of the highly acid-resistant ceramic glaze material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0023] Embodiment 1: A highly acid-resistant ceramic glaze material comprises the following raw materials in parts by weight: 1.0 part of boron nitride nanosheets, 10 parts of fluorine-doped titanium oxide, 1.0 part of calcium fluoride, 15.0 parts of kaolinite, 20.0 parts of feldspar, 40 parts of aluminum oxide, 15 parts of zirconium oxide, 5 parts of silicon carbide, 2.0 parts of sodium fluorosilicate, 5 parts of borax, 20 parts of kaolin, 2.0 parts of calcium phosphate, 5.0 parts of polymethyl methacrylate balls, 2 parts of ammonium polyacrylate, and 30 parts of deionized water; The average diameter of the polymethyl methacrylate ball is 3.0 μm; the surface of the ceramic glaze material has micro-convex bodies with a lotus leaf-like structure; the average gap between the micro-convex bodies is 2.5 μm, the average height is 8 μm, and the average diameter is 15 μm. The doping amount of fluorine in the fluorine-doped titanium oxide is 0.5 wt%.

[0024] The preparation method of boron nitride nanosheets is as follows: by weight, 2.5 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 180 parts of deionized water are added, and the interlayer exfoliation is achieved at an ultrasonic frequency of 38kHz for 110 minutes, followed by centrifugation at 3000rpm for 8 minutes to remove the unexfoliated layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, and ethanol and deionized water are used to wash the suspension alternately for 3 times at a volume ratio of 1:3, with the amount of solvent used for each washing being 40mL / g of nanosheet, and the boron nitride nanosheet is dried in a vacuum drying oven at 55°C and -0.08MPa for 4.0h to obtain the boron nitride nanosheet. The preparation method of intercalated boron nitride is as follows: by weight, 1.0 parts of hexagonal boron nitride powder and 18.0 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 780°C at a rate of 8°C / min under nitrogen atmosphere protection and kept warm for 3.5 hours to complete the intercalation reaction, and cooled to room temperature to obtain intercalated boron nitride. The thickness of the boron nitride nanosheet is 0.6nm and the lateral size is 0.8μm.

[0025] The preparation method of fluorine-doped titanium oxide is as follows: 4.5 parts of fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 400°C at 3°C / min under a nitrogen atmosphere, kept warm for 2 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5μm. The preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 1.0 parts of titanium tetrachloride and 50 parts of deionized water are mixed, and stirred for 10 minutes under a magnetic stirrer at 300 rpm to form a transparent solution; 0.5 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 0.1 mol / L, the dropping speed is controlled to be 0.1 mL / min, and the pH of the system is simultaneously adjusted to 2.0; the mixed solution is transferred to a high-pressure reactor, heated to 120°C at 2°C / min, and maintained for 12 hours for hydrothermal reaction; after cooling to 25°C, the precipitate is separated by a centrifuge at 8000 rpm for 5 minutes, and the supernatant is discarded; the precipitate is washed alternately 3 times with deionized water and ethanol at a volume ratio of 1:1, and the amount of solvent used for each washing is 30 mL / g of the precipitate; the washed product is placed in a vacuum drying oven, and dried for 6 hours at 60°C and -0.05 MPa to obtain a fluorine-doped titanium oxide precursor.

[0026] The method for preparing a highly acid-resistant ceramic glaze material of the present embodiment comprises the following steps: S1. Alumina, zirconium oxide, and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added, and the ball-to-material ratio is controlled at 3:1. The mixture is milled at a ball milling rate of 400 rpm for 2 h. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate, and borax are added, and the ball milling rate is reduced to 200 rpm. The mixture is mixed for 2 h. After the ball milling is completed, the resulting suspension is filtered through a 200-mesh sieve to remove large particle impurities and set aside. S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 300 rpm for 2 h using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing 40 kHz ultrasonic treatment for 30 min to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 300 rpm for 1 hour to evenly distribute them in the slurry. After stirring, let it stand for 30 minutes to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is uniformly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 80 μm. After coating, the sample is pre-frozen in an environment of -50°C and sublimated and dried at 0.1 Pa for 12 hours; S5. The freeze-dried sample was placed in a tube furnace and pyrolyzed in a nitrogen atmosphere in steps. First, the temperature was raised to 300°C at a heating rate of 1°C / min and kept at this temperature for 2 hours to decompose part of the organic template. Then, the temperature was raised to 500°C at the same heating rate and kept at this temperature for another 2 hours to ensure that the polymethyl methacrylate balls were completely decomposed. Then, the heating rate was reduced to 3°C / min and the temperature was continued to be raised to 1150°C and kept at this temperature for 2 hours to achieve the densification of the glaze layer. S6. Slowly cool the sintered sample to 600°C, and continue to cool to room temperature at a cooling rate of 2°C / min. Subsequently, place the obtained ceramic glaze layer sample in a 0.5 mol / L sodium fluorosilicate solution and soak for 30 minutes. After the treatment is completed, take out the sample, bake it at 150°C for 1 hour, and cool it to room temperature.

[0027] Depend on Figure 1 It can be seen that the surface of the highly acid-resistant ceramic glaze material prepared by the present invention successfully constructs a lotus leaf-like micro-convex structure, which forms a micro-nanoscale double roughness, effectively reduces the surface energy, and provides a physical basis for achieving excellent hydrophobic properties. Figure 2 It shows that water droplets present a typical high contact angle spherical morphology on the surface of the glaze layer, further proving the superhydrophobic properties of the material. This bionic microstructure combined with the chemical regulation of fluorine-doped titanium oxide not only enables the glaze layer to have excellent acid resistance, but also effectively reduces the adhesion of pollutants and achieves a long-term self-cleaning effect. In summary, the experimental results fully verify the innovation and practical value of the present invention, and provide reliable technical support for the application of ceramic glaze materials in the fields of high acid resistance and self-cleaning.

[0028] Embodiment 2: A highly acid-resistant ceramic glaze material, comprising the following raw materials in parts by weight: 1.5 parts of boron nitride nanosheets, 13 parts of fluorine-doped titanium oxide, 1.5 parts of calcium fluoride, 19.5 parts of kaolinite, 26.0 parts of feldspar, 46 parts of aluminum oxide, 18 parts of zirconium oxide, 8 parts of silicon carbide, 3.2 parts of sodium fluorosilicate, 7 parts of borax, 23 parts of kaolin, 4.4 parts of calcium phosphate, 6.5 parts of polymethyl methacrylate balls, 3 parts of ammonium polyacrylate, and 36 parts of deionized water; The average diameter of the polymethyl methacrylate spheres is 3.9 μm; the ceramic glaze material has micro-convex bodies with a lotus leaf-like structure on the surface; the average gap between the micro-convex bodies is 3.3 μm, the average height is 9 μm, and the average diameter is 18 μm. The fluorine doping amount in the fluorine-doped titanium oxide is 1.3 wt%.

[0029] The preparation method of boron nitride nanosheets is as follows: by weight, 3.4 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 192 parts of deionized water are added, and the interlayer exfoliation is achieved at an ultrasonic frequency of 39kHz for 116 minutes, followed by centrifugation at 3600rpm for 9 minutes to remove the unexfoliated layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, and ethanol and deionized water are used to wash the suspension alternately for 4 times in a volume ratio of 1:3, with the amount of solvent used for each washing being 46mL / g of nanosheet, and the boron nitride nanosheet is dried in a vacuum drying oven at 58°C and -0.09MPa for 4.6 hours to obtain the boron nitride nanosheet. The preparation method of intercalated boron nitride is as follows: by weight, 1.3 parts of hexagonal boron nitride powder and 19.2 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 792°C at a rate of 9°C / min under nitrogen atmosphere and kept warm for 3.8 hours to complete the intercalation reaction, and cooled to room temperature to obtain intercalated boron nitride. The thickness of the boron nitride nanosheet is 0.8nm and the lateral size is 2.2μm.

[0030] The preparation method of fluorine-doped titanium oxide is as follows: 5.7 parts by weight of fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 460°C at 5°C / min under a nitrogen atmosphere, kept warm for 3 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5μm. The preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 2.2 parts of titanium tetrachloride and 80 parts of deionized water are mixed, and stirred for 16 minutes under a magnetic stirrer at 360 rpm to form a transparent solution; 1.3 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 0.4 mol / L, the dropping speed is controlled to be 0.2 mL / min, and the pH of the system is simultaneously adjusted to 2.6; the mixed solution is transferred to a high-pressure reactor, heated to 138°C at 3°C / min, and maintained for 19 hours for hydrothermal reaction; after cooling to 28°C, the precipitate is separated by a centrifuge at 9200 rpm for 8 minutes, and the supernatant is discarded; the precipitate is washed alternately 4 times with deionized water and ethanol at a volume ratio of 1:1, and the amount of solvent used for each washing is 36 mL / g of precipitate; the washed product is placed in a vacuum drying oven, and dried at 66°C and -0.07 MPa for 8 hours to obtain a fluorine-doped titanium oxide precursor.

[0031] The method for preparing a highly acid-resistant ceramic glaze material of the present embodiment comprises the following steps: S1. Alumina, zirconium oxide and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added, the ball-to-material ratio is controlled at 3:1, and the ball milling speed is 430 rpm for 3 hours. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate and borax are added, the ball milling speed is reduced to 215 rpm, and the mixing is continued for 2 hours. After the ball milling is completed, the obtained suspension is filtered through a 260-mesh screen to remove large particle impurities and set aside; S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 330 rpm for 3 h using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing 46 kHz ultrasonic treatment for 35 min to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 390 rpm for 2 h to evenly distribute them in the slurry. After stirring, let it stand for 39 min to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is evenly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 92 μm. After coating, the sample is pre-frozen in a -47°C environment and sublimated and dried at 0.1 Pa for 16 hours; S5. The freeze-dried sample was placed in a tube furnace and pyrolyzed in a nitrogen atmosphere in steps. First, the temperature was raised to 306°C at a heating rate of 1°C / min and kept at this temperature for 2 hours to decompose part of the organic template. Then, the temperature was raised to 515°C at the same heating rate and kept at this temperature for another 2 hours to ensure that the polymethyl methacrylate balls were completely decomposed. Then, the heating rate was reduced to 4°C / min and the temperature was continued to be raised to 1165°C and kept at this temperature for 3 hours to achieve the densification of the glaze layer. S6. Slowly cool the sintered sample to 660°C, and continue to cool to room temperature at a cooling rate of 3°C / min. Subsequently, place the obtained ceramic glaze layer sample in a 1.0 mol / L sodium fluorosilicate solution and soak for 39 minutes. After the treatment is completed, take out the sample, bake it in an environment of 165°C for 2 hours, and cool it to room temperature.

[0032] Embodiment 3: A highly acid-resistant ceramic glaze material, comprising the following raw materials in parts by weight: 1.9 parts of boron nitride nanosheets, 16 parts of fluorine-doped titanium oxide, 1.9 parts of calcium fluoride, 24.0 parts of kaolinite, 32.0 parts of feldspar, 52 parts of aluminum oxide, 21 parts of zirconium oxide, 11 parts of silicon carbide, 4.4 parts of sodium fluorosilicate, 8 parts of borax, 26 parts of kaolin, 6.8 parts of calcium phosphate, 8.0 parts of polymethyl methacrylate balls, 4 parts of ammonium polyacrylate, and 42 parts of deionized water; The average diameter of the polymethyl methacrylate spheres is 4.8 μm; the ceramic glaze material has micro-convex bodies with a lotus leaf-like structure on the surface; the average gap between the micro-convex bodies is 4.0 μm, the average height is 10 μm, and the average diameter is 21 μm. The fluorine doping amount in the fluorine-doped titanium oxide is 2.0 wt%.

[0033] The preparation method of boron nitride nanosheets is as follows: by weight, 4.3 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 204 parts of deionized water are added, and the interlayer exfoliation is achieved at an ultrasonic frequency of 40kHz for 122 minutes, followed by centrifugation at 4200rpm for 10 minutes to remove the unexfoliated layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, and ethanol and deionized water are used to wash the suspension alternately for 4 times in a volume ratio of 1:3, with the amount of solvent used for each washing being 52mL / g of nanosheet, and the boron nitride nanosheet is dried in a vacuum drying oven at 61°C and -0.09MPa for 5.2h to obtain the boron nitride nanosheet. The preparation method of intercalated boron nitride is as follows: by weight, 1.6 parts of hexagonal boron nitride powder and 20.4 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 804°C at a rate of 10°C / min under nitrogen atmosphere protection and kept warm for 4.1 hours to complete the intercalation reaction, and cooled to room temperature to obtain intercalated boron nitride. The thickness of the boron nitride nanosheet is 1.0nm and the lateral size is 3.6μm.

[0034] The preparation method of fluorine-doped titanium oxide is as follows: 6.9 parts by weight of fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 520°C at 6°C / min under a nitrogen atmosphere, kept warm for 4 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5μm. The preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 3.4 parts of titanium tetrachloride and 110 parts of deionized water are mixed, and stirred for 22 minutes under a magnetic stirrer at 420 rpm to form a transparent solution; 2.0 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 0.6 mol / L, the dropping speed is controlled to be 0.3 mL / min, and the pH of the system is simultaneously adjusted to 3.2; the mixed solution is transferred to a high-pressure reactor, heated to 156°C at 4°C / min, and maintained for 26 hours for hydrothermal reaction; after cooling to 31°C, the precipitate is separated by a centrifuge at 10400 rpm for 11 minutes, and the supernatant is discarded; the precipitate is washed alternately 4 times with deionized water and ethanol at a volume ratio of 1:1, and the amount of solvent used for each washing is 42 mL / g of the precipitate; the washed product is placed in a vacuum drying oven, and dried for 10 hours at 72°C and -0.08 MPa to obtain a fluorine-doped titanium oxide precursor.

[0035] The method for preparing a highly acid-resistant ceramic glaze material of the present embodiment comprises the following steps: S1. Alumina, zirconium oxide and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added, and the ball-to-material ratio is controlled at 3:1. The ball milling speed is 460 rpm for 3 hours. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate and borax are added, and the ball milling speed is reduced to 230 rpm. The mixing is continued for 3 hours. After the ball milling is completed, the obtained suspension is filtered through a 320-mesh screen to remove large particle impurities and set aside; S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 360 rpm for 3 h using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing 52 kHz ultrasonic treatment for 39 min to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 480 rpm for 2 h to evenly distribute them in the slurry. After stirring, let it stand for 48 min to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is evenly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 104 μm. After coating, the sample is pre-frozen in a -44°C environment and sublimated and dried at 0.1 Pa for 20 h; S5. The freeze-dried sample was placed in a tube furnace and pyrolyzed in a nitrogen atmosphere in steps. First, the temperature was raised to 312°C at a heating rate of 2°C / min and kept at this temperature for 3 hours to decompose part of the organic template. Then, the temperature was raised to 530°C at the same heating rate and kept at this temperature for another 3 hours to ensure that the polymethyl methacrylate balls were completely decomposed. Then, the heating rate was reduced to 4°C / min and the temperature was continued to be raised to 1180°C and kept at this temperature for 3 hours to achieve densification of the glaze layer. S6. Slowly cool the sintered sample to 720°C, and continue to cool to room temperature at a cooling rate of 4°C / min. Subsequently, place the obtained ceramic glaze layer sample in a 1.4 mol / L sodium fluorosilicate solution and soak for 48 minutes. After the treatment is completed, take out the sample, bake it in an environment of 180°C for 2 hours, and cool it to room temperature.

[0036] Embodiment 4: A highly acid-resistant ceramic glaze material, comprising the following raw materials in parts by weight: 2.5 parts of boron nitride nanosheets, 20 parts of fluorine-doped titanium oxide, 2.5 parts of calcium fluoride, 30.0 parts of kaolinite, 40.0 parts of feldspar, 60 parts of aluminum oxide, 25 parts of zirconium oxide, 15 parts of silicon carbide, 6.0 parts of sodium fluorosilicate, 10 parts of borax, 30 parts of kaolin, 10.0 parts of calcium phosphate, 10.0 parts of polymethyl methacrylate balls, 5 parts of ammonium polyacrylate, and 50 parts of deionized water; The average diameter of the polymethyl methacrylate ball is 6.0 μm; the surface of the ceramic glaze material has micro-convex bodies with a lotus leaf-like structure; the average gap between the micro-convex bodies is 5.0 μm, the average height is 12 μm, and the average diameter is 25 μm. The doping amount of fluorine in the fluorine-doped titanium oxide is 3wt%.

[0037] The preparation method of boron nitride nanosheets is as follows: by weight, 5.5 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 220 parts of deionized water are added, and the interlayer exfoliation is achieved at an ultrasonic frequency of 42kHz for 130 minutes, followed by centrifugation at 5000rpm for 12 minutes to remove the unexfoliated layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, and ethanol and deionized water are used to wash the suspension alternately for 5 times in a volume ratio of 1:3, with the amount of solvent used for each washing being 60mL / g of nanosheet, and the boron nitride nanosheet is dried in a vacuum drying oven at 65°C and -0.10MPa for 6.0h to obtain the boron nitride nanosheet. The preparation method of intercalated boron nitride is as follows: by weight, 2.0 parts of hexagonal boron nitride powder and 22.0 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 820°C at a rate of 12°C / min under nitrogen atmosphere protection and kept warm for 4.5 hours to complete the intercalation reaction, and cooled to room temperature to obtain intercalated boron nitride. The thickness of the boron nitride nanosheet is 1.2nm and the lateral size is 5.5μm.

[0038] The preparation method of fluorine-doped titanium oxide is as follows: 8.5 parts of fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 600°C at 8°C / min under a nitrogen atmosphere, kept warm for 6 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5μm. The preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 5.0 parts of titanium tetrachloride and 150 parts of deionized water are mixed, and stirred for 30 minutes under a magnetic stirrer at 500 rpm to form a transparent solution; 3.0 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 1.0 mol / L, the dropping speed is controlled to be 0.5 mL / min, and the pH of the system is simultaneously adjusted to 4.0; the mixed solution is transferred to a high-pressure reactor, heated to 180°C at 5°C / min, and maintained for 36 hours for hydrothermal reaction; after cooling to 35°C, the precipitate is separated by a centrifuge at 12000 rpm for 15 minutes, and the supernatant is discarded; the precipitate is washed alternately 5 times with deionized water and ethanol in a volume ratio of 1:1, and the amount of solvent used for each washing is 50 mL / g of the precipitate; the washed product is placed in a vacuum drying oven, and dried for 12 hours at 80°C and -0.10 MPa to obtain a fluorine-doped titanium oxide precursor.

[0039] The method for preparing a highly acid-resistant ceramic glaze material of the present embodiment comprises the following steps: S1. Alumina, zirconium oxide, and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added, and the ball-to-material ratio is controlled at 3:1. The ball milling speed is 500 rpm for 4 hours. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate, and borax are added, and the ball milling speed is reduced to 250 rpm. The mixing is continued for 3 hours. After the ball milling is completed, the resulting suspension is filtered through a 400-mesh sieve to remove large particle impurities and set aside; S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 400 rpm for 4 hours using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing 60 kHz ultrasonic treatment for 45 minutes to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 600 rpm for 3 hours to evenly distribute them in the slurry. After stirring, let it stand for 60 minutes to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is uniformly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 120 μm. After coating, the sample is pre-frozen in an environment of -40°C and sublimated and dried at 0.1 Pa for 24 hours; S5. The freeze-dried sample was placed in a tube furnace and pyrolyzed step by step under a nitrogen atmosphere. First, the temperature was raised to 320°C at a heating rate of 2°C / min and kept at this temperature for 3 h to decompose part of the organic template. Then, the temperature was raised to 550°C at the same heating rate and kept at this temperature for another 3 h to ensure that the polymethyl methacrylate balls were completely decomposed. Then, the heating rate was reduced to 5°C / min and the temperature was continued to be raised to 1200°C and kept at this temperature for 4 h to achieve the densification of the glaze layer. S6. Slowly cool the sintered sample to 800°C, and continue to cool to room temperature at a cooling rate of 5°C / min. Subsequently, place the obtained ceramic glaze layer sample in a 2.0 mol / L sodium fluorosilicate solution and soak for 60 minutes. After the treatment is completed, take out the sample, bake it at 200°C for 3 hours, and cool it to room temperature.

[0040] Comparative Example 1 It is basically the same as Example 1, except that boron nitride nanosheets are not used, which leads to a decrease in the corrosion resistance of the glaze layer in acidic media, obvious corrosion pits appearing on the surface, increased water absorption, and reduced density of the glaze layer structure.

[0041] Comparative Example 2 It is basically the same as Example 1, except that the fluorine-doped titanium oxide has not been subjected to hydrothermal treatment, resulting in uneven fluorine doping, which reduces the acid resistance and hydrophobicity of the material, reduces the water droplet contact angle, and makes pollutants on the glaze layer surface easy to adhere.

[0042] Comparative Example 3 It is basically the same as Example 1, except that ultrasonic exfoliation is not used to prepare boron nitride nanosheets, but blocky boron nitride powder is directly added, resulting in poor dispersion of nanosheets, uneven glaze layer structure, and significantly reduced acid resistance and self-cleaning performance.

[0043] Comparative Example 4 It is basically the same as Example 1, except that the sintering temperature of fluorine-doped titanium oxide is reduced from 600°C to 400°C, resulting in insufficient crystallinity of titanium oxide, poor doping stability, reduced acid resistance of the glaze layer, and poor self-cleaning effect.

[0044] Comparative Example 5 It is basically the same as Example 1, except that the surface treatment with sodium fluorosilicate is not performed, resulting in a higher surface energy of the glaze layer, a lower water drop contact angle, a significantly reduced hydrophobic performance, and a weakened self-cleaning ability.

[0045] Comparative Example 6 It is basically the same as Example 1, except that the ratio of alumina to zirconia is reduced by 50%, resulting in a decrease in the mechanical strength of the glaze layer, a decrease in wear resistance, and a significant increase in surface roughness after the Taber wear test.

[0046] Comparative Example 7 It is basically the same as Example 1, except that polymethyl methacrylate balls are not used as the template, which leads to a reduction in the micro-nano pore structure of the glaze layer, a decrease in the surface roughness, a decrease in the hydrophobic property, and a weakened self-cleaning effect.

[0047] Comparative Example 8 It is basically the same as Example 1, except that the ratio of kaolin and feldspar is adjusted to 2:1, which leads to an aggravated phase separation phenomenon during sintering, reduced uniformity of the glaze layer, and decreased acid resistance and mechanical strength.

[0048] Comparative Example 9 It is basically the same as Example 1, except that the sintering temperature of the glaze is reduced from 1200° C. to 1000° C., resulting in a decrease in the density of the glaze layer and a decrease in corrosion resistance. SEM observation shows that the surface porosity increases.

[0049] Comparative Example 10 It is basically the same as Example 1, except that silicon carbide is not added to the glaze layer, resulting in reduced thermal shock resistance of the glaze layer in a high temperature environment, obvious cracks appearing after the hot and cold cycle test, and reduced material stability.

[0050] Performance Testing: Acid corrosion test: The prepared ceramic glaze material samples were immersed in hydrochloric acid and sulfuric acid solutions of different concentrations (such as 1M, 3M, 6M) and placed at a constant temperature (60°C) for 72 hours. Before and after the test, the acid resistance of the material was evaluated by weighing the sample mass change, observing the surface morphology with a scanning electron microscope (SEM), and analyzing the chemical composition changes with X-ray photoelectron spectroscopy (XPS).

[0051] Hydrophobicity test: Determine the contact angle of a water droplet according to ASTMD 7334-08. Use a contact angle meter (such as the Krüss DSA series) to drop deionized water on the sample surface and record the change in the contact angle of the water droplet. A contact angle above 150° indicates that the material has super hydrophobic properties. In addition, an inclination angle test can be performed to measure the rolling performance of water droplets at different inclination angles to further verify the self-cleaning ability.

[0052] Wear performance test: Wear resistance test was conducted according to ASTM C501 standard. The glaze layer was subjected to 5000 friction cycles using Taber abrasion tester (CS-10 grinding wheel, 1kg load). The surface roughness change was measured before and after the test, and the wear area was analyzed using SEM to evaluate the wear resistance of the material and the stability of the micro-convex structure.

[0053] Self-cleaning performance test: Spray simulated pollutants (such as methyl blue solution or carbon black suspension) evenly on the sample surface and place it under ultraviolet light (365nm, 10mW / cm 2) or natural light conditions, the degradation of pollutants was measured regularly, and the changes in pollutant concentrations were monitored by ultraviolet-visible (UV-Vis) spectroscopy to evaluate the photocatalytic self-cleaning effect of the material.

[0054] The properties of the glazes of Examples 1 to 4 and Comparative Examples 1 to 10 are summarized in Table 1.

[0055] Acid resistance is affected by the degree of surface fluorination and microstructure. Uneven fluorine doping or no surface fluorination will reduce hydrophobicity, making acid more permeable, resulting in decreased acid resistance. The microconvex structure may form a gas buffer layer to hinder acid penetration, thereby improving acid resistance. The self-cleaning performance is mainly affected by the photocatalytic activity. TiO 2 Insufficient crystallinity will reduce the ability to degrade pollutants. In addition, the optimization of the surface microstructure may indirectly enhance the self-cleaning performance, and even if the photocatalytic active components are missing, a high pollutant removal rate can still be maintained. Wear resistance is greatly affected by the proportion of hard phases. The reduction of aluminum oxide and zirconium oxide content will reduce the hardness of the material, increase the roughness change, and reduce wear resistance. At the same time, the stability of the micro-convex structure also plays an important role in long-term wear resistance.

[0056] Table 1 Performance of glazes of Examples 1 to 4 and Comparative Examples 1 to 10

[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A highly acid-resistant ceramic glaze material, characterized in that: The invention comprises the following raw materials in parts by weight: 1.0-2.5 parts of boron nitride nanosheets, 10-20 parts of fluorine-doped titanium oxide, 1.0-2.5 parts of calcium fluoride, 15.0-30.0 parts of kaolinite, 20.0-40.0 parts of feldspar, 40-60 parts of aluminum oxide, 15-25 parts of zirconium oxide, 5-15 parts of silicon carbide, 2.0-6.0 parts of sodium fluorosilicate, 5-10 parts of borax, 20-30 parts of kaolin, 2.0-10.0 parts of calcium phosphate, 5.0-10.0 parts of polymethyl methacrylate balls, 2-5 parts of ammonium polyacrylate, and 30-50 parts of deionized water; The average diameter of the polymethyl methacrylate spheres is 3.0-6.0 μm; The surface of the ceramic glaze material has micro-convex bodies imitating a lotus leaf structure; The micro-convex bodies have an average gap of 2.5-5.0 μm, an average height of 8-12 μm, and an average diameter of 15-25 μm. The doping amount of fluorine in the fluorine-doped titanium oxide is 0.5-3 wt%.

2. A highly acid-resistant ceramic glaze material as claimed in claim 1, characterized in that: The preparation method of the boron nitride nanosheets is as follows: by weight, 2.5-5.5 parts of intercalated boron nitride are transferred to an ultrasonic reactor, 180-220 parts of deionized water are added, and the interlayer peeling is achieved at an ultrasonic frequency of 38-42kHz for 110-130min, followed by centrifugation at 3000-5000rpm for 8-12min to remove the unpeeled layered aggregates and retain the supernatant; the supernatant is separated by a vacuum filtration device to obtain a boron nitride nanosheet suspension, ethanol and deionized water are used to alternately wash 3-5 times at a volume ratio of 1:3, the amount of solvent used for each washing is 40-60mL / g nanosheet, and the boron nitride nanosheet is dried in a vacuum drying oven at 55-65°C and -0.08--0.10MPa for 4.0-6.0h to obtain the boron nitride nanosheet.

3. A highly acid-resistant ceramic glaze material as claimed in claim 2, characterized in that: The preparation method of the intercalated boron nitride is as follows: by weight, 1.0-2.0 parts of hexagonal boron nitride powder and 18.0-22.0 parts of potassium hydroxide are placed in a corundum crucible and mixed evenly, heated to 780-820°C at a rate of 8-12°C / min under nitrogen atmosphere protection and kept warm for 3.5-4.5h to complete the intercalation reaction, and cooled to room temperature to obtain the intercalated boron nitride.

4. A highly acid-resistant ceramic glaze material as claimed in claim 2, characterized in that: The boron nitride nanosheet has a thickness of 0.6-1.2 nm and a lateral size of 0.8-5.5 μm.

5. The highly acid-resistant ceramic glaze material according to claim 1, characterized in that: The preparation method of the fluorine-doped titanium oxide is as follows: 4.5 to 8.5 parts by weight of a fluorine-doped titanium oxide precursor are placed in a tube furnace, heated to 400 to 600 °C at 3 to 8 °C / min under a nitrogen atmosphere, kept warm for 2 to 6 hours, then naturally cooled to room temperature, and ground to a particle size of ≤5 μm.

6. A highly acid-resistant ceramic glaze material as claimed in claim 5, characterized in that: The preparation method of the fluorine-doped titanium oxide precursor is as follows: by weight, 1.0-5.0 parts of titanium tetrachloride and 50-150 parts of deionized water are mixed, and stirred for 10-30 min at 300-500 rpm on a magnetic stirrer to form a transparent solution; 0.5-3.0 parts of ammonium fluoride solution are added dropwise, wherein the concentration of the ammonium fluoride solution is 0.1 to 1.0 mol / L, the dropping speed is controlled to be 0.1-0.5 mL / min, and the pH of the system is simultaneously adjusted to 2.0-4.0; The mixed solution was transferred to a high-pressure reactor, heated to 120-180 °C at a rate of 2-5 °C / min, and maintained for 12-36 h for hydrothermal reaction; after cooling to 25-35 °C, the precipitate was separated by a centrifuge at 8000-12000 rpm for 5-15 min, and the supernatant was discarded; the precipitate was washed alternately with deionized water and ethanol in a volume ratio of 1:1 for 3-5 times, and the amount of solvent used for each washing was 30-50 mL / g of precipitate; the washed product was placed in a vacuum drying oven, and dried at 60-80 °C and -0.05-0.10 MPa for 6-12 h to obtain a fluorine-doped titanium oxide precursor.

7. The method for preparing a highly acid-resistant ceramic glaze material according to claim 1, characterized in that: The following steps are involved: S1. Alumina, zirconium oxide and silicon carbide are mixed in proportion, placed in a ball mill, deionized water is added to control the ball-to-material ratio to 3:1, and the ball milling speed is 400-500 rpm for 2-4 hours. Subsequently, fluorine-doped titanium oxide, calcium fluoride, kaolinite, feldspar, kaolin, calcium phosphate and borax are added, and the ball milling speed is reduced to 200-250 rpm. The mixture is mixed for 2-3 hours. After the ball milling is completed, the obtained suspension is filtered through a 200-400 mesh screen to remove large particle impurities and set aside. S2. Adding boron nitride nanosheets to the suspension obtained in step S1, adding ammonium polyacrylate, and then grinding at 300-400 rpm for 2-4 hours using a high-energy ball milling assisted exfoliation method using zirconium oxide grinding balls. After grinding, performing an ultrasonic treatment at 40-60 kHz for 30-45 minutes to further evenly disperse the boron nitride nanosheets; S3. Slowly add polymethyl methacrylate balls to the uniformly dispersed mixed slurry obtained in step S2, stir at a stirring rate of 300-600 rpm for 1-3 hours to evenly distribute them in the slurry. After stirring, let it stand for 30-60 minutes to release the bubbles in the slurry and improve the uniformity of subsequent coating; S4. The slurry obtained in step S3 is uniformly coated on the surface of the ceramic substrate, and the wet film thickness is controlled to be 80-120 μm. After coating, the sample is placed in a -50--40°C environment for pre-freezing, and sublimation drying is performed at 0.1 Pa for 12-24 hours; S5. The freeze-dried sample was placed in a tube furnace and pyrolyzed in a nitrogen atmosphere in steps. First, the temperature was raised to 300-320°C at a heating rate of 1-2°C / min and kept at this temperature for 2-3 hours to decompose part of the organic template. Then, the temperature was raised to 500-550°C at the same heating rate and kept at this temperature for another 2-3 hours to ensure that the polymethyl methacrylate balls were completely decomposed. Then, the heating rate was reduced to 3-5°C / min and the temperature was continued to be raised to 1150-1200°C and kept at this temperature for 2-4 hours to achieve the densification of the glaze layer. S6. Slowly cool the sintered sample to 600~800℃, and continue to cool to room temperature at a cooling rate of 2~5℃ / min. Subsequently, place the obtained ceramic glaze layer sample in a 0.5~2.0mol / L sodium fluorosilicate solution and soak for 30~60min. After the treatment is completed, take out the sample, bake it in an environment of 150~200℃ for 1~3h, and cool it to room temperature.

Citation Information

Patent Citations

  • Ceramic glaze

    CN107804973A

Cited By

  • Soft-light wear-resistant antiskid glazed tile and preparation method thereof

    CN121248326A